Two-dimensional flow properties of micronozzle under varied isothermal wall conditions. (1st January 2013) - Hameed, Amar Hasan; Kafafy, Raed; Asrar, Waqar; Idres, Moumen
A new technology, which uses thermoelectric elements as side-walls of microthrusters for heating and cooling purpose, is emerging. This technique can improve the performance of low-Reynolds-number microthrusters as a result of increasing the flow momentum forces or decreasing the viscous forces. In the present paper, we focus on the effect of using heated or cooled walls to control the properties of the flow through a micronozzle. Viscous compressible laminar flow is solved in the micronozzle. Different isothermal divergent-wall temperatures are tested to study the impact of wall temperature on the fundamental properties of momentum forces. The temperature difference between the wall and the gas effects the static temperature and static pressure profile, Mach number is increased, density near the wall is increased due to cooling. Alleviation of viscous losses by cooling the supersonic flow in the expander is demonstrated by the reduction of the thickness of the subsonic boundary layer.